Assessment of Seed Producer Associations in Uganda - Namanda, S.; McEwan, M.; Rajendran, S.; Oloka, B.; Namazzi, S. (International Potato Center, 2021)
In Uganda, until recently, more institutionalized local seed production chain was limited to seed grains such as cereals and legumes and, to limited extent, vegetables. Over the past two decades, several initiatives have emerged to promote production of clean planting for both seed grains and plant parts of vegetatively propagated crops (VPCs), including sweetpotato. Initial efforts by partners (including line NGOs, public and private sectors, and farmers) have been made to establish active chain structures for production and dissemination of early generation to quality-declared seed. Uganda’s national seed policy was reviewed to include VPCs for inspection and certification, piloted through established regional registered seed producer associations for sweetpotato planting material. Interventions continue to focus on improving the seed production and dissemination of clean planting for improved crop productivity. The International Potato Center (CIP), through its SweetGAINS program, is currently implementing sustainable, inclusive seed systems for accelerated dissemination and adoption of market-preferred varieties in the Kamuli district in eastern Uganda. For this work to be successful, there must be an understanding of work and operations of established seed producer associations (SPAs) – which is the purpose of this report. By investigating the on-going seed-related activities in this region, we can better inform and develop proposed interventions to improve seed systems for these farmers and, eventually, throughout Uganda. Our key focus would be on improving capacity of SPAs to learn and support seed system protocols for ensuring high-quality, disease-free seed with strong links between farmers and the marketplace. Due to COVID-19, our interviews were taken over the telephone with randomly-selected 13 irrespective of crop focus. From these interviews, we conclude the following major points (which are elaborated in details and supported with evidence in this report): 1. Many SPAs deal with more than one seed crop 2. NGOs in the area are providing support to solve logistical, inspection-related and certification related challenges; From these observations, we make the following recommendations: 1. To enhance the capacity of SPAs to use clean seed in their respective areas of operation; 2. To encourage diversified seed incomes by focusing on multiple crops; 3. To enable phasal withdrawal of selected NGOs to drive more SPAs to be self-sustaining; and 4. To develop stronger knowledge among SPAs of market demands, business planning, and internal seed inspection. The full set of recommendations with explanation are available in section 3.0.